Attracting skilled immigrants: an overview of recent policy developments in advanced countries - Facchini, Giovanni; Lodigiani, Elisabetta (Sage, 2014)
In this paper we review the policies put in place by the main Western destination countries to attract highly skilled migrants. Two main systems can be identified. On the one hand, employer-driven schemes typically call for the migrant to meet a set of minimum skill requirements and to have a job offer before a work visa can be issued. On the other, employee driven schemes typically do not require a job offer, and instead select the migrant based on a set of characteristics chosen by the policy maker. Employer driven schemes are the dominant policy tool in the sample of countries we consider in the analysis, and only Australia, Canada and New Zealand have made employee-driven schemes the mainstay of their skill selective immigration policy. The preliminary evidence we review suggests that the latter are more effective in increasing the skill level of the immigrant population, and casts doubts on the usefulness of new initiatives like the EU blue card that are still based on an employer driven system.